2018
DOI: 10.1016/j.foodchem.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of soy protein hydrolysates with antioxidant activity by using peptidases from latex of Maclura pomifera fruits

Abstract: A partially purified proteolytic extract prepared from Maclura pomifera latex was employed in hydrolyzing a soybean-protein isolate (4.2 mg/mL). The hydrolysis-product formation, monitored by tricine-sodium-dodecyl-sulfate-polyacrylamyde-gel electrophoresis and reverse-phase high-performance liquid chromatography, indicated that after 10 min of reaction the main soybean proteins disappeared. The maximum degree of hydrolysis was 36.2% after a 180-min digestion. The 90-min hydrolysate presented an IC of 31.6 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…Nowadays, there is a large number of studies reported about antioxidant peptides from caseins of different sources, such as bovine, buffalo (Shazly et al., 2017), ovine (Gómez‐Ruiz et al., 2008), camel (Jrad et al., 2014), and caprine (Bezerra et al., 2013), which propose their use as both ingredients for functional food or as nutraceuticals. The TEAC value corresponding to our casein hydrolysate (after180 min at 55°C) was higher than those published for a buffalo casein hydrolysate (0.86 μM/mg; Shanmugam et al., 2015), a bovine casein hydrolysate (0.16 μM/mg; Reyes Jara et al., 2018), and a fermented bovine milk (0.66 μM/mg; Padghan et al., 2018), and therefore, we consider that our casein 180 min‐hydrolysate could be useful as a source of antioxidative peptides for the food industry.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Nowadays, there is a large number of studies reported about antioxidant peptides from caseins of different sources, such as bovine, buffalo (Shazly et al., 2017), ovine (Gómez‐Ruiz et al., 2008), camel (Jrad et al., 2014), and caprine (Bezerra et al., 2013), which propose their use as both ingredients for functional food or as nutraceuticals. The TEAC value corresponding to our casein hydrolysate (after180 min at 55°C) was higher than those published for a buffalo casein hydrolysate (0.86 μM/mg; Shanmugam et al., 2015), a bovine casein hydrolysate (0.16 μM/mg; Reyes Jara et al., 2018), and a fermented bovine milk (0.66 μM/mg; Padghan et al., 2018), and therefore, we consider that our casein 180 min‐hydrolysate could be useful as a source of antioxidative peptides for the food industry.…”
Section: Resultscontrasting
confidence: 67%
“…Soybean proteins were isolated from active defatted soybean flour (Bunge, Buenos Aires, Argentina), using the method reported by Reyes Jara et al. (2018); whey protein was exuded and collected by clotting bovine milk as was described by Bertucci et al. (2015); and casein substrate was prepared by dissolving 1.25 g of casein in 100 mL of 0.1 M phosphate buffer (pH 6.4).…”
Section: Methodsmentioning
confidence: 99%
“…Bioactive peptides have been widely used in health-food, nutraceuticals, and pharmaceutical preparations due to their significant biological functions and efficient absorption [1]. As one of several promising bioactive peptides, antioxidant peptides have become a topic of great interest because of the association between many human diseases and oxidative stress [2]. When humans are subjected to oxidative stress, large amounts of reactive oxygen species (ROS) are produced.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it presents a variety of biological activities responsible for lowering cholesterol, acting as antioxidants, and improving hypertension. [5][6][7][8] At present, most of the research on prebiotics focuses on carbon sources such as fructooligosaccharides and xylooligosaccharides and oen ignore the inuence of nitrogen sources on probiotics. [9][10][11] Nitrogen sources are essential for the growth of probiotics, and an insufficient nitrogen source leads to the decelerated growth and metabolism of the probiotics even when the high-dose carbon source is supplemented.…”
Section: Introductionmentioning
confidence: 99%